MEMAKSIMALKAN ILMU SYAR’I TANPA MELUPAKAN AMAL (KAJIAN TASAWUF): MAXIMIZING SYAR'I KNOWLEDGE WITHOUT FORGETTING CHARITIES - Muzakkir Yayyibe (IAI DDI Mangkoso, 2022)
This research aims to describe science and charity and the substance of both, with the formulation of the main problem; 1. How to maximize knowledge 2. What is meant by Sharia knowledge and the nature of Sharia knowledge 3. The focus of the problem in this paper is Science and Charity which then becomes the subfocus 1. The essence of knowledge and charity 2. Prioritizing knowledge over charity 2. No ignore one of the two. This research is qualitative research using the library research method. Data collection focuses on books, scriptures and scientific articles related to the subject matter being studied. From the research results, it was concluded that knowledge and charity are two inseparable components in the perspective of Sufism, prioritizing knowledge over charity. It is not permissible to neglect knowledge because of charity and it is not permissible to neglect charity because of knowledge.